Synthesis and Characterization of Acetate Based Ionic Liquid for CO2 Removal - Mohd Fauzi bin Yean, Mohd Fauzi (Universiti Teknologi Petronas, 2011)
This report basically discusses the preliminary research done and basic understanding of “Synthesis and Characterization of Acetate Based Ionic Liquid for CO2 Removal”. This project aims at simulation modeling for studying the CO2 solubility and its behavior towards ionic liquids at room temperature with variable pressure condition. The simulation process part is currently running by using special software for simulation of ionic liquid called COSMO-RS software. The simulation process is selecting two types of ionic liquid which are 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-butyl-3methylimidazolium acetate as a sample solution for CO2 removal. This report basically remains consist of four sections. The first section is on the introduction part of the project including background study of the project, problem statement, objectives and scope of study and relevancy of project. The next section is on the literature review. In this section, there will be a brief theory on the ionic liquids regarding the characteristics, conditions and experimental data from journal for CO2 solubility in ionic liquids. Then this report followed by third chapter which is methodology that covers on the steps and process flow of simulation using COSMO-RS software for examining two selected types of ionic liquids. Lastly in final section which is result and discussion part for complete simulation process regarding the selected ionic liquids. Final results are presented by validating some parameters such as interaction energy and sigma profile for completion of simulation data regarding the particular types of ionic liquids that has been selected earlier.